Respostas

A melhor resposta!
2014-08-18T19:48:47-03:00
Olá!

f(x) = 2x^3 - 1\\\\
f(0) = 2*0^3 - 1\\
f(0) = -1\\
\\
f(-1) = 2*(-1)^3 - 1\\
f(-1) = 2*(-1) - 1\\
f(-1) = -2 -1\\
f(-1) = -3\\
\\
f(2) = 2*2^3 - 1\\
f(2)=2*8-1\\
f(2) = 16 -1\\
f(2) = 15\\
\\\\
f(0) + f(-1) + f(2) = 0\\
-1 + (-3) + 15 = -4 + 15 = 11

Espero que tenha ajudado!
5 5 5
2014-08-18T19:49:49-03:00
F(x)=2x³-1              f(x)=2x³-1               f(x)=2x³-1      
f(0)=2(0)³-1            f(-1)=2(-1)³-1           f(2)=2.2³-1 
f(0)=0-1                f(-1)= -2-1               f(2)=16-1
f(0)=0                   f(-1)= -3                 f(2)=15

0+(-3)+15= 0-3+15  = 15

3 3 3
ta errado man
comu q 2³ da 16
kkkkkkk